The sensitivity of distributional measures to the reference period of income - Carsten Schröder (Kiel Institute for the World Economy (IfW), 2012)
When individual or household incomes are collected for administrative or scientific surveys, the reference period of income is sometimes a month, sometimes a quarter, and sometimes a year. This reference period of income likely affects the shape of the distribution and derived measures of inequality, poverty, and mobility. Using employment histories of German residents, the present study systematically explores the sensitivity of distributional measures to the length of the reference period of income. Estimates from annual, quarterly and monthly distributions are provided for one and a half decades, starting from year 1991.
Keywords: D1; D31; I32; 330; inequality; poverty; mobility; reference period of income; monthly; quarterly; and annual distributions; earnings; Germany; Soziale Ungleichheit; Armut; Disparitätsmaß; Einkommensstatistik; Statistische Methode; Zeit; Schätzung; Deutschland